High Performance Pt Nanocatalysts for the Oxidation of Methanol and Ethanol in Acid Media by Effect of Functionalizing Carbon Supports with Ru Organometallic Compounds. Issue 16 (24th November 2020) - Martínez-Loyola, J. C.; Siller-Ceniceros, A. A.; Sánchez-Castro, M. E.; Sánchez, M.; Torres-Lubián, J. R.; Escobar-Morales, B.; Ornelas, C.; Alonso-Lemus, I. L.; Rodríguez-Varela, F. J.
Abstract : The Intermittent Microwave Heating (IMH) assisted polyol method was used to disperse Pt nanoparticles on Vulcan XC-72 (C) and reduced Graphene Oxide (rGO) functionalized with [( η 6 -C6 H5 OCH2 CH2 OH)RuCl2 ]2 ( Ru-dim ) and [( η 6 -C6 H4 (CHMe2 )Me)RuCl2 ]2 ( Ru-cym ). The nanocatalysts were labeled as Pt/CRu-dim, Pt/CRu-cym, Pt/rGORu-dim and Pt/rGORu-cym . Their catalytic activity was evaluated for the Methanol (MOR) and Ethanol Oxidation Reactions (EOR). 1 H and APT 13 C NMR characterization showed the coordination of arene ligands with ruthenium atoms, supporting the formation of Ru-dim and Ru-cym . Raman spectroscopy indicated that C and rGO preserve their graphitic band structure after functionalization. Functionalization of the supports resulted in the development of several surface chemical groups. The electrochemical characterization showed that: i) Pt/CRu-dim was the nanocatalyst with the highest catalytic activity for the MOR, demonstrating also a high performance for the EOR; ii) Pt/rGORu-cym showed a good electrocatalytic behavior for both reactions at more negative potentials, nevertheless delivering lower current densities (j). In terms of the organic molecule, higher j values have been obtained from the MOR, compared to the EOR. The results showed that these nanocatalysts can be considered as anode materials in Direct Alcohol Fuel Cells applications.